Corbett papers: biographical, legal, & contextual material on the life & career of Jim Corbett of Kumaon - Shah, Akshay (ed.); Alter, Stephen (ed.) (Delhi Black Kite, 2022)
In this book, author share his experiences with wildlife in the jungles of North India. It also includes the unpublished reminiscences of Jim by his sister Maggie, and rare extracts from a forgotten work.
Keywords: Jim Corbett; Tiger hunting